Pengaruh Pendidikan Terhadap Jiwa Keagamaan - Yazidul Busthomi; Syamsul A’dlom (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2019)
The role of education in influencing one's religious attitudes and soul is enormous. It is shown in everyday life that looks real. Because basically a human being was born with the basic potential, and then the potential is developed with education. The importance of education in influencing one's religious life can be likened to someone who without education will be the same as an animal will be even more ugly than the animal. The environment is also an education as well as society. Because it affects attitude and personality. Attitude and personality can be combined with the term soul. Moreover education has a great influence on the religious soul that arises on a person. Because the religious soul of a person is greatest influenced by the factor of education. The development of a person's psyche is a form of reasonableness and must occur within a person. Therefore education is a necessity in directing the process of psychological development. Moreover in Islamic educational institutions, it will affect the formation of his religious soul. This religious soul needs to be implanted in children from an early age. Religious education is a form of value education, therefore the maximum and absence of religious education depends on factors that can motivate to understand the value of religion. The more the atmosphere of religious education to make it so that the development of religious soul will be able to grow optimally. This religious soul will grow together with the ambience of the surrounding environment. When the religious soul has grown it will form a religious attitude manifested in everyday life.